A Study on Effect of Various Bracing Systems in Rc Frame Structure Using Staad Pro (International Journal of Innovative Research in Engineering & Management, 2022)
When a tall building is subjected to  earthquake under the action of lateral loads. Providing a  suitable lateral force resisting system has a significant effect  on the performance of the RC frame structure. The present  study focuses on the study of bracing systems for RC frame  structure. The effectiveness of different types of bracing on  the RC frame structure has been carried out. For this study,  a G+13 storied RC frame structure has been considered and  structural behavior has been studied at three seismic zones  (III, IV and V). The RC frame structure models are  analyzed by Response spectrum and equivalent static  method as per IS 1893:2016 (part1) using STAAD Pro  software. The structural behavior has been studied using  different types of bracing systems such as X bracing,  Diagonal bracing, Chevron bracing and Eccentric bracing.  A comparative study has been done on parameters story  displacement, story drift, base shear, axial force, weight of  the structure between braced and un-braced RC frame  model. From the study, it has been observed that the lateral  displacement and story drift of the braced system decrease  in the structure as compared to the un-braced frame in all  seismic zones (III, IV and V). Bending moment values in  braced frame model get reduced and axial force value in the  braced frame model increase as compared to unbraced  frame model. It is concluded that the X bracing  significantly contribute to structure stiffness as compared to  the other bracing system.
Keywords: Various Bracing Systems; Rc Frame; Structure